Techno-economic study of the impact of mirror slope errors on the overall optical and thermal efficiencies- case study: Solar parabolic trough concentrator evaluation under semi-arid climate. (December 2020) - El Ydrissi, Massaab; Ghennioui, Hicham; Bennouna, El Ghali; Farid, Abdi
Abstract: In this paper, a techno-economic study of the impact of mirror slope errors is achieved. The geometric and optical efficiencies of a parabolic trough collector, installed at Green Energy Park research facility, are studied. Following, yields analysis of a 1MWe power plant is conducted and modeled under semi-arid climate. The plant is simulated by considering the geometric and optical proprieties of the studied parabolic trough collector and using high-quality meteorological data measured at ground level for one year. Finally, an economic investigation is presented, taking the Levelized Cost of Electricity as an indicator. According to the results, the global average mirror slope errors measured by the robust deflectometry technique are 4.59 mrad. The calculated experimental optical efficiency is then 65.4%. Consequently, the optical efficiency drop of the studied collector due to theses slope errors is 12.44%. Based on the simulation results of the modeled power plant, the monthly average electrical losses due to the impact of mirror slope errors can reach 20.53 MWhe . The results of the economic evaluation showed that 12.44% of optical efficiency increased the LCOE by 14.14%. Therefore, the quality specifications and assessment of collectors before and during solar field assembly are important. Highlights: Geometric, optical, and thermal performances of the studied PTC are evaluated. A 1 MWe power plant is modeled considering experimental mirror slope errors. The impact of mirror slope errors on plant performances is investigated. Economic analysis is presented, taking the LCOE as an indicator. . 12.44% of optical efficiency drop increased the LCOE by approximately 14.14%.